Way Down South: The milliped family Parajulidae (Julida: Parajulini) in Mexico and Central America; first records from El Salvador and the Baja California Peninsula - Shelley, Rowland M. (Zootaxa, 2008)
Accounts and drawings are presented of all established species of the Parajulini with extant types and genitalia, which appear to comprise nine species groups, four with available generic names. Parajulus Humbert & de Saussure, 1869, and Thriniulus Chamberlin, 1940, contain only the respective type species, P. olmecus Humbert & de Saussure, 1869, and T. leucoclius (Chamberlin, 1922). Both Mexicoiulus Verhoeff, 1926, and Pheniulus Chamberlin, 1943, contain the respective types, M. dampfi Verhoeff, 1926, and Pheniulus phenotypus Chamberlin, 1943, and, tentatively, two additional species. No new combinations are proposed, so except for the four types, all species are temporarily placed in "Parajulus." Thriniulus schachti Chamberlin, 1941, is returned to "Parajulus," and Pheniulus mimeticus Chamberlin, 1943, is transferred into it. "Parajulus" zempoalus Chamberlin, 1943, and "P." gyratus, Loomis, 1971, are reduced to subspecies of "P." pueblanus and "P." rosanus, both by Chamberlin, 1943, respectively. "Parajulus" schmidti Chamberlin, 1952, comprises two subspecies, the nominate and "P." s. australis, n. subsp., from El Salvador, a new country for both the tribe and family and the southernmost indigenous record for the Julida in the Western Hemisphere. New state records include "Parajulus" p. pueblanus, n. stat., from Veracruz, "P." r. gyratus from Puebla and Hidalgo, and "P." viganus Chamberlin, 1952, from Hidalgo. The distribution of the Parajulidae in North America is detailed, and the family and tribe Bollmaniulini are newly recorded from the Baja California peninsula. Lectotype designation is formalized for Parajulus aztecus Pocock, 1903.